Augmented Reality Navigation System (SIRIO) for Neuroprotection in Vertebral Tumoral Ablation - Eliodoro Faiella; Rebecca Casati; Matteo Pileri; Giuseppina Pacella; Carlo Altomare; Elva Vergantino; Amalia Bruno; Bruno Beomonte Zobel; Rosario Francesco Grasso (Current Oncology)
(1) This study evaluates the impact of the CT-guided SIRIO augmented reality navigation system on the procedural efficacy and clinical outcomes of neuroprotection in vertebral thermal ablation (RTA) for primary and metastatic bone tumors. (2) Methods: A retrospective non-randomized analysis of 28 vertebral RTA procedures was conducted, comparing 12 SIRIO-assisted and 16 non-SIRIO-assisted procedures. The primary outcomes included dose-length product (DLP) and epidural dissection time. The secondary outcomes included technical success, complication rates, and pain scores at procedural time (VAS Time 0) and three months post-procedure (VAS Time 1). The statistical analyses included t-tests, Mann–Whitney U tests, and multiple regression. (3) Results: SIRIO-assisted procedures significantly reduced DLP (307.42 mGycm vs. 460.31 mGycm, p = 2.23 × 10−8) and procedural epidural dissection time (13.48 min vs. 32.26 min, p = 2.61 × 10−12) compared to non-SIRIO-assisted procedures. Multiple regression confirmed these reductions were significant (DLP: β = −162.38, p < 0.001; time: β = −18.25, p < 0.001). Pain scores (VAS Time 1) did not differ significantly between groups, and tumor type did not significantly influence outcomes. (4) Conclusions: The SIRIO system enhances neuroprotection efficacy and safety, reducing radiation dose and procedural time during spine tumoral ablation while maintaining consistent pain management outcomes.